Evaluation of teacher training programs and their outputs according to the overall quality standards from the point of view of faculty members (Field study at Tishreen University College of Education) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
•  This research aims to identify the characteristics of the future teacher and the requirements of preparation, especially in the light of global variables and changing roles in the era of technology and scientific and cultural development, and then know the reality of teacher education programs in the Faculty of Education, Tishreen University,And to stand at the approved methods and methods adopted by the teaching staff in the rehabilitation of the teacher grade, in order to develop these programs in light of the new educational roles of teachers. In order to prepare a scale for the evaluation of teacher preparation programs in accordance with the requirements of international quality systems in order to achieve reform of the newly graduated teacher, in view of the teacher is the cornerstone and starting point in the development and modernization of the educational process and thus get the appropriate outputs qualified qualification required. The following:The percentage of indicators achieved in the specifications of the student teacher from the point of view of the bite of the faculty ranged between (12.5%) and (75%) and the average percentage was (27.33%), indicating that the program of teacher education and its outputs in the professional field did not satisfy And that there is a need to review the objectives of this area, its content and the methods of providing it to the students.The percentage of indicators achieved in the specifications of the student teacher from the point of view of the faculty member ranged between (12.5%) and (50%) and the average percentage reached (26.13%) indicating that the teacher education program and its outputs in the social-personal field did not achieve The great satisfaction required for the beneficiaries of this program, which indicates the need to review the objectives of this area and content and methods for students The research came out with a number of proposals,• The need to keep up with global changes and achieve quality requirements as an essential step for school reform• The importance of preparing and qualifying teachers at the Arab and local level according to international quality systems• Adopt the proposed scale as a tool to evaluate teacher training programs in Syrian education colleges.